Effect of rehabilitation on knee joint function after injury and arthroscopic reconstruction of the anterior cruciate ligament - Ewa Wawrukiewicz; Stanisław Krajewski; Łukasz Bielawa; Rafał Gotowski; Krystian Wawrukiewicz (Kazimierz Wielki University, 2018)
Breaking the continuity of the ACL and a long-term loss of its function may lead to the destruction of deep feeling receptors and thereby an abolition of joint feeling. After injury, a person has a feeling of joint's instability and feels fear of burdening the limb. This injury may provide to the damage of cartilage and menisci and as a result it leads to arthrosis development. The aim of this thesis was the analysis of rehabilitation method and its influence on a daily functioning of a knee joint among patients after the arthroscopic anterior cruciate ligament reconstruction from gracillis and semitendinosus tendons. As a hypothesis, I have assumed a thesis, that the rehabilitation program selected properly, including elements of deep feeling and strengthening training, may reset a good function of a knee joint, enabling the patient a return to activities before injury. The research included the examination of 30 patients at the age from 18 to 56 years. Patients were operated arthroscopically because of the anterior instability of a knee joint after the previous cruciate ligament injury. The clinical evaluation was performed with an application of a range of motion measurement by the SFTR method using goniometer," front drawer "test and Lovett test. The second method of clinical evaluation was an application of subjective scales evaluating the function of a knee joint and complaints, which exist after the reconstruction: Lysholm scale. In this research, a questionnaire is applied to evaluate the method of rehabilitation as well as an application of physiotherapeutic and kinesitherapeutic procedures and, above all, proproceptive training. After the statistical analysis of collected materials, it is confirmed that a knee function after the arthroscopic anterior cruciate ligament reconstruction was subjectively evaluated by 90% examined as a "good" result or "very good". For the majority of examined, 74% patients return to sports activities before injury without meaningful complaints. Kinesitherapy carried out properly, taking into account the proprioceptive training and strengthening training, is more important after the ACL reconstruction than a long duration of rehabilitation.